2021
DOI: 10.1080/19490976.2021.2003176
|View full text |Cite
|
Sign up to set email alerts
|

Combined berberine and probiotic treatment as an effective regimen for improving postprandial hyperlipidemia in type 2 diabetes patients: a double blinded placebo controlled randomized study

Abstract: Non-fasting lipidemia (nFL), mainly contributed by postprandial lipidemia (PL), has recently been recognized as an important cardiovascular disease (CVD) risk as fasting lipidemia (FL). PL serves as a common feature of dyslipidemia in Type 2 Diabetes (T2D), albeit effective therapies targeting on PL were limited. In this study, we aimed to evaluate whether the therapy combining probiotics (Prob) and berberine (BBR), a proven antidiabetic and hypolipidemic regimen via altering gut microbiome, could effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 76 publications
0
22
0
1
Order By: Relevance
“…The hypoglycemic effect of this traditional Chinese medicine may be partly attributed to one of its main components, BBR. Clinical studies have demonstrated that BBR not only exerts a hypoglycemic effect by regulating the structure and function of the human gut microbiota, but also improves fasting and postprandial lipidemia in T2D patients to achieve better cardiovascular risk control ( 30 , 31 ). Animal experiments have also shown that BBR has important potential in the treatment of diabetes-related complications such as diabetic nephropathy ( 32 , 33 ), diabetic retinopathy ( 34 , 35 ), diabetic cardiomyopathy ( 36 ), diabetic encephalopathy ( 37 ) and diabetic neuropathy ( 38 ) by inhibiting inflammation and oxidative stress, anti-endothelial injury, regulating glucose and lipid metabolism, inhibiting microvascular proliferation and regulating autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The hypoglycemic effect of this traditional Chinese medicine may be partly attributed to one of its main components, BBR. Clinical studies have demonstrated that BBR not only exerts a hypoglycemic effect by regulating the structure and function of the human gut microbiota, but also improves fasting and postprandial lipidemia in T2D patients to achieve better cardiovascular risk control ( 30 , 31 ). Animal experiments have also shown that BBR has important potential in the treatment of diabetes-related complications such as diabetic nephropathy ( 32 , 33 ), diabetic retinopathy ( 34 , 35 ), diabetic cardiomyopathy ( 36 ), diabetic encephalopathy ( 37 ) and diabetic neuropathy ( 38 ) by inhibiting inflammation and oxidative stress, anti-endothelial injury, regulating glucose and lipid metabolism, inhibiting microvascular proliferation and regulating autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine, an isoquinoline alkaloid extracted from the Chinese herb Coptidis rhizoma (Huanglian), demonstrated multiple biological functions, including anti-inflammatory and anti-bacterial effects, alleviation of liver fibrosis, inhibition of carcinogenesis, cardiometabolic protection, as well as neuroprotection [89][90][91][92].…”
Section: Berberinementioning
confidence: 99%
“…Além disso, 02 (dois) estudos com Berberina foram avaliados na presente revisão (Wang et al 2021 Foi analisado 01 (um) artigo que avaliou a eficácia das fibras dietéticas no manejo da sintomatologia da DM2 (ZHAO et al 2018), que demonstrou que houve redução significativa de hemoglobina glicada, glicose em jejum e HOMA-IR. O impacto do exercício físico na microbiota foi avaliado em 01 (um) artigo (Motiani et al 2019) mostrando aumento de Butirato, redução de hemoglobina glicada e glicose em jejum, não sendo avaliado índice HOMA nesse estudo.…”
Section: Aspectos Metabólicos E Fisiopatológicos Do Dmunclassified